EFEK RESIDU PEMUPUKAN NPK BERBASIS AMONIUM DAN NITRAT TERHADAP KETERSEDIAAN HARA, KELIMPAHAN BAKTERI SERTA PERTUMBUHAN DAN HASIL TANAMAN SAWI - Nur Fitria Dwi Retno Anggraini; Yulia Nuraini; Cahyo Prayogo (Departemen Tanah, Fakultas Pertanian, Universitas Brawijaya, 2017)
NPK fertilizer residue can positively affect the improvement of soil nutrients and increase crop production, but the negative impact to the soil and plant growth can also be caused by fertilizer unmanaged NPK fertilizer. The aim of this study was to determine the residual effect of NPK fertilizer based combination of ammonium nitrate and NPK petrobiofertile on availability of nutrients in the second cropping season. Treatment tested were residue of 400 kg ha-1 of NPK 25-7-7 with additional nitrate as much as 1%, 2% and 3% and fertilizer combinations Petrobiofertil 100 kg ha-1. Results showed that the treatments significantly affected the content of mineral N at 20 days after planting at a depth of 0-20 cm and at 40 days after planting at 0-20 cm and 20-40 cm depths, Â but the results were not significant at a depth of 20-40 cm at 20 days after planting. N concentration at 40 days after planting at a depth of 0-20 cm was significantly different high at P4 treatment. Concentrations of total K was significant at 20 days after planting at a depth of 0-20 cm and 20-40 cm and at 40 days after planting at 20-40 cm depth. The treatments also results in a significant number of bacterial colonies on 20 days after planting and 40 days after planting. Plant height, leaf number, leaf area, fresh consumption significant weight at 20 until 40 days after planting. N uptake was also significant at 20 and 40 days after planting